Pengaruh Gaya Hidup dan Promosi terhadap Keputusan Pembelian Layanan â€œMusic Spotify Premiumâ€ Studi Kasus pada Generasi Milenial di Bali - Kadeari, Ni Luh Eni; Heryanda, Komang Krisna (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to test the influence of lifestyle and promotion on the decision to purchase Spotify Premium service to Millennials in Bali both simultaneously and partially. The research method used is a caesal quantitative research method. The sampling technique used is Purposive Sampling, with a total sample of 75 respondents. Data analysis techniques used are multiple linear regression analysis. Data collection instruments using questionnaires. The results of this study are: (1) Lifestyle and promotion have a significant influence on the decision to purchase Music Spotify Premium service to millennials in Bali, (2) Lifestyle has a significant influence on the decision to purchase Spotify Premium Music service to millennials in Bali, (3) Promotion has a positive and significant effect on the decision to purchase Spotify Premium Music service to millennials in Bali.